PENGEMBANGAN MATERI BAHASA INGGRIS UNTUK ANAK USIA DINI DI PAUD PELANGI GUYANGAN - Aprilia Riyana Putri (Universitas Islam Nahdlatul Ulama Jepara)
Teaching material is learning medium which is used for making the teaching and learning process easier. The purpose of this research is developing teaching material with Modul as a product in teaching English based on the quality, criteria and standard. The process for developing material is tested to the students guided by the teacher. The result from the test shows the score or value which is made by the students. That data is analyzed by the reviewer in details. The result from reviewer shows that it involves good category with the average score 3, 89. The highest criterion is in writing technique category in designing teaching material. The result from the test is on four numbers, such as : in good design, interesting writing and color, good images and interesting writing and also making the students are easier to understand English materials with the average score 116,7 Keywords: Pengembangan Materi, Bahasa Inggris, Anak Usia Dini